Factors associated with mental disorders in long-settled war refugees: a study in refugees from Ex-Yugoslavia in Germany, Italy and the United Kingdom - Bogić, Marija (Array, 2012)
Prevalence rates of mental disorders are frequently increased in longsettled war refugees. However, substantial variation of prevalence rates across studies and countries remains unexplained. To test whether the same socio-demographic characteristics, war experiences and post-migration stressors are associated with mental disorders in similar refugee groups resettled in different countries. Mental disorders were assessed in war-affected refugees from former Yugoslavia in Germany, Italy and the United Kingdom. Socio-demographic, warrelated and post-migration characteristics were tested for their association with different disorders. 854 war refugees were assessed (≥255 per country). Prevalence rates of mental disorders varied substantially across countries. Lower education, more traumatic experiences during and after the war, more migration-related stress, a temporary residence permit, and not feeling accepted were independently associated with higher rates of mood and anxiety disorders. Mood disorders were also associated with older age, female sex, and being unemployed, and anxiety disorders with the absence of combat experience. Higher rates of PTSD were associated with older age, lower education, more traumatic experiences during and after the war, absence of combat experience, more migration-related stress, and a temporary residence permit. Only younger age, male sex and not living with a partner were associated with substance useuse disorders. The associations did not differ significantly across the 4 countries. War-related factors explained more variance in rates of PTSD, and postmigration factors in the rates of mood, anxiety and substance use disorder. Socio-demographic characteristics, war experiences and post-migration stressors are independently associated with mental disorders in long-settled war refugees. The risk factors vary for different disorders, but are consistent across host countries for the same disorders.